Multimediation Method With Balanced Repeated Replications For Analysis Of Complex Surveys. Issue 5 (3rd September 2019) - Mai, Yujiao; Ha, Trung; Soulakova, Julia N.
Abstract : We propose a method suitable for analysis of cross-sectional studies with complex sampling and continuous variables. The method consists of R + 4 steps, where R denotes the number of replications. In the first R + 1 step, the main and R replicate weights are used (one at a time) to estimate the product of coefficients for all mediation effects using a structural equation model. In step R + 2, the standard errors of these estimates are computed via balanced repeated replications. In step R + 3, the raw p values corresponding to mediation effects are computed based on the generalized Sobel's tests. In the final step, R + 4, the p values are adjusted for multiplicity and statistical inferences regarding mediation effects are drawn. To illustrate the approach we examined significance of attitudes toward smoking bans as mediators in the association between smoking restrictions at work and nicotine dependence among male daily smokers.